Physical ground for radioactive waste transmutation facility using thermonuclear neutrons - Rudychev, Y.V.; Khazhmuradov, M.A.; Slabospitskiy, R.P. (Вопросы атомной науки и техники, 2009)
Two variants of radioactive waste transformation system using thermonuclear neutrons were considered. In one case transuranium elements and fission products are irradiated together and in second one they are irradiated separately. Advantages and disadvantages of each case were analyzed. Second variant was chosen. Physical basing of facility construction for radioactive waste elements transmutation using thermonuclear neutrons for such variant was developed. Розглядається два варіанти системи трансмутації радіоактивних відходів за допомогою термоядерних нейтронів. В одному - трансуранові елементи та продукти ділення не відокремлені один від одного, в іншому варіанті опромінюються роздільно. Проаналізовано переваги та недоліки кожного з варіантів. Перевага віддана другому варіанту і для нього виконано фізичне обґрунтування елементів конструкції установки, що розробляється. Рассматривается два варианта системы трансмутации радиоактивных отходов с помощью термоядерных нейтронов. В одном - трансурановые элементы и продукты деления не отделены друг от друга, в другом варианте облучаются раздельно. Проанализированы преимущества и недостатки каждого из вариантов. Предпочтение отдано второму варианту и для него выполнено физическое обоснование элементов конструкции разрабатываемой установки.